Genetic-Phenotypic Variability and Correlation between Morphology-Anatomy-Physiology Characteristics and Dry Matter Yield of Polyploidized Forage Grasses under Aluminum Stressed Condition - Anwar, S (ANIMAL PRODUCTION, 2007)
The study was conducted with the aim to know the genetic-phenotypic variability (heritability value), and correlation between morphology-anatomy-physiology characters and dry matter yield (DMY) of polyploidized forage grasses under aluminum (Al) stressed condition.  A total of 16 forage grass genotypes (polyploid and diploid Brachiaria brizantha, Brachiaria decumbens, Setaria sphacelata, Setaria splendida, Panicum muticum, Panicum maximum, Pennisetum purpureum, and Pennisetum purpupoides) were subjected to Al-stressed (16 mM Al2(SO4)3).  The treatments were allotted to a Randomized Completely Block Design with monofactorial pattern (genotypes) and 5 blocks in each treatment.  The morphology-anatomy-physiology characteristics evaluated were plant height, leaf number, tiller number, leaf color, chlorophyll content, stomata number, chloroplast number, leaf nitrate reductase activity, dry matter,  wet matter yield, dry matter yield, stress tolerance index and pH media.  Results showed the polyploidization increased stress tolerance index of grasses.  The genetic-phenotypic variability (heritability value) estimates for all morphology-anatomy-physiology characteristics were high.  Most morphology-anatomy-physiology characteristics, except leaf number, chlorophyll content and chloroplast number, had significant correlation to dry matter yield. In conclusion, evaluation on selection progress of dry matter yield of forage grasses can be effectively done by selection for yield of wet matter, plant height, leaf color, branch number, stomata number, leaf nitrate reductase activity, pH media, and dry matter simultaneously. (Animal Production 9(1): 23-29 (2007) Key Words: selection, genetic-phenotypic variability, forage grass, aluminum stress